Early Use of Magnetic Endoscopic Imaging by Novice Colonoscopists: Improved Performance without Increase in Workload - Sylvain Coderre; John Anderson; Remy Rikers; Paul Dunckley; Karen Holbrook; Kevin McLaughlin (Canadian Journal of Gastroenterology)
BACKGROUND: Magnetic endoscopic imaging represents a recent advance in colonoscopy training. This technique provides adjunct information to the endoscopist, specifically with regard to colonoscope loop formation.